The role of personality on work-related attitudes and behaviour of early childhood educators and care providers : a thesis in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Barrow, Christine (Massey University, 1999)
The present study aimed to provide a personality profile of early childhood educators and care providers in New Zealand and to assess their psychological well-being. This may be the first attempt within New Zealand to provide an empirical frame-work from which the personality profile of the early childhood educator and care provider can be described. The study examined how well personality traits can predict the work-related attitudes and behaviours of affective and continuance commitment, self-rated performance, global job satisfaction, psychological well-being, and performance as assess by co-worker or supervisor. Results from the study give tentative support for the personality factor of agreeableness being able to distinguish the 'good' early childhood educator and care provider from others. The study utilised quantitative data, collected through a survey. Questionnaire One comprised three personality scales, including the NEO PI-R, five scales to measure outcome, and collected a range of demographic data. Questionnaire Two was handed to a co-worker to rated the participants performance. There were 416 Questionnaire One's returned and 340 of these were matched to Questionnaire Two. An aggregate personality profile of the participants was formed. The level of diminished psychological well-being was consistent with that of a normal sample of adults. Results indicated that personality was a moderate predictor of the attitudes and behaviour examined. Work locus of control was the better predictor of affective and continuance commitment and job satisfaction. General work self-efficacy was the better predictor of self-rated performance, and neuroticism was the better predictor of psychological well-being. The study further analysed the predictive ability of personality using multiple regression analysis. Results showed that affective and continuance commitment could substantially increase the explained variance in job satisfaction after controlling for personality traits. Further, the present study showed there are significant differences in some aspects of the personality profile of early childhood educators and care providers in terms of the position held within the centre, the centre type, and if employed part-time or full-time. Sub-group differences need to be considered when using personality to predict outcomes.
Keywords: Psychology; Preschool teachers; Early childhood educators; Child care workers